Penilaian Greenship dalam Penerapan Material Resource and Cycle pada Kafe Kopi Break di Kota Makassar - Arinda Wahyuni; Gusti Hardyanti Musda (Universitas Muslim Indonesia, 2024)
The application of reusing used materials as building materials in Indonesia is an effort to create environmentally friendly architecture. One example of using used materials is using zinc roofing material or plastic drink boxes. Used tin roofs may not be waste that damages the environment, because used tin roofs can be reused and recycled. Therefore, zinc roofing material is reused on buildings, making the building unique and environmentally friendly and helping to preserve the environment. The aim of this research is to identify and assess Cafe Kopi Break buildings that use used zinc roofing materials based on the Source and Material Cycle criteria of the Greenship Green Building Council Indonesia (GBCI). In this research, the research methodology used is a qualitative methodology in the form of field surveys and interviews. The analysis carried out refers to the Material Source and Cycle criteria according to Greenship GBCI which includes Foundational Refrigerants, Use of Used Buildings and Materials, Environmentally Friendly Materials, Use of Refrigerants without ODP, Prefabricated Materials, and Regional Materials. Based on the results of the analysis, it can be concluded that Cafe Kopi Break meets the total percentage of 79% of the assessment based on the Material Source and Cycle criteria in the GBCI Greenshp